Chapter Il Divino amore dalla mistica teologia del sec. XIV alla pietà romana del Settecento - Corrubolo, Federico (Fragmentaria. Studi di storia culturale e antropologia religiosa, 2020)
This paper shows in its essential points the development of spiritual doctrine of divine love in Italy during four centuries (1350-1750 AD), especially regarding religious ambients, some authors and main texts produced in Florence, Venice, Genoa and Rome. The author explains various steps of diffusion of the spirituals ideas connected to the theology of divine love, and indicates some important writers and ambients whcich had a particular relief concerning this topic. A particular interesting is reserved to a religious order called povari yesuati, that is the principal promoter of this particular devotion, especially promoted by Domenico da Monticchiello and his italian translation of an important work of Hugh of Balma, called "mistica teologia". The povari yesuati is an religious order not many known but very important in cultural and religious world of late middle age in Italy. It's also mentioned the origin of Roman sanctuary of our Lady of Divine Love, that is also at the present and many important religious sanctuary for the people of Rome.